PP25 The take home naloxone intervention multicentre emergency setting feasibility (TIME) trial: an early perspective from one UK ambulance service. Issue 9 (19th August 2021) - Johnston, Sasha; Snooks, Helen; Jones, Jenna; Bell, Fiona; Benger, Jonathan; Black, Sarah; Dixon, Simon; Edwards, Adrian; Evans, Bridie; Fuller, Gordon; Goodacre, Steve; Hoskins, Rebecca; et al.
Abstract : Background: Drug poisoning deaths in England and Wales have increased by 52% since 2011 with over half involving opioids. Deaths are preventable if naloxone is administered in time. Take Home Naloxone (THN) kits have been distributed through drug services; however, uptake is low and effectiveness unproven. The TIME trial tests the feasibility of conducting a full randomised controlled trial of providing THN administration and basic life support training to high-risk opioid-users in emergency care settings. Methods: A multi-site feasibility trial commenced in June 2019 with two hospitals and their surrounding ambulance services (Bristol Royal Infirmary (BRI) with South Western Ambulance NHS Foundation Trust (SWASFT) and Hull Royal Infirmary with Yorkshire Ambulance Service) randomly allocated to intervention arms; and sites in Wrexham and Sheffield allocated as 'usual care' controls. SWASFT began recruiting in October 2019 with the aim of recruiting and training 50% (n=111) of paramedics working within the BRI's catchment area, to supply THN to at least 100 eligible patients during a 12-month period. Results: The trial was suspended between 17.03.2020-06.08.2020 and extended to 01.03.2021 (COVID-19). Despite this, 121 SWASFT paramedics undertook TIME training. TIME trained paramedics attended 30% (n=57) of the n=190 opioid-related emergency calls requiring naloxone administration during the study period. A total of n=29 potentially eligible patients were identified before and n=28 after the COVID-19 suspension. Two patients were supplied with THN during each period. During the COVID-19 suspension, twenty-two potentially eligible patients were missed. The majority of eligible patients presented with a reduced consciousness level, preventing recruitment (73%; n=42/48). These patients were transported to hospital for further treatment (n=39) or died on scene following advanced life support (n=3). Conclusions: The lowered consciousness levels of prehospital emergency ambulance patients who present with opioid poisoning, often prevent the delivery of training required to enable the supply of THN.